Star Wars : Ewoks - Orlando, Steve (Comic book writer) (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2025)
"A team of Imperial-led bounty hunters and scavengers arrives on the forest moon of Endor searching for a secret cache of deadly weaponry! But are they prepared to face off against the battle-ready Ewoks who took down so many of their ranks? Plus: Who is the mysterious new warrior Ewok returning to Bright Tree Village, and what is their connection to Wicket W. Warrick?"--